2019
DOI: 10.1002/2050-7038.12206
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear controller for maximum power extraction in asymmetric multilevel DC link reduced switch count inverter‐based grid connected PV system

Abstract: Summary This paper presents the grid integration of reduced switch count (RSC)‐based asymmetric Multilevel DC‐Link (MLDCL) inverter for photovoltaic (PV) system. Among the recently reported reduced switch count multilevel inverter (RSC‐MLI) topologies, MLDCL possess modularity, switching redundancies and fault tolerant capability. MLDCL can achieve multilevel output with significant reduction in switch count as compared to cascade H‐bridge (CHB). Similar to CHB, the structure of MLDCL allows to develop a commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…PWM technique is classified as; n-phase disposition (IPD), Anti-phase disposition (APD), Carrier Overlap (CO) and Variable Frequency (VF) are used in MLI's [19][20][23][24]. The (n-l) carriers are used to match with the modulation signal in an n-level inverter, in MC-PWM [20,25].…”
Section: Pwm Modulation Techniquementioning
confidence: 99%
“…PWM technique is classified as; n-phase disposition (IPD), Anti-phase disposition (APD), Carrier Overlap (CO) and Variable Frequency (VF) are used in MLI's [19][20][23][24]. The (n-l) carriers are used to match with the modulation signal in an n-level inverter, in MC-PWM [20,25].…”
Section: Pwm Modulation Techniquementioning
confidence: 99%
“…The authors had concluded that the DC grid has the advantages of simple construction and high reliability. The novel work of Reference 9 proposed a reduced switch count‐based multilevel inverter for integrating solar PV systems into the grid. The authors 10 developed a novel switching capacitor‐based multilevel inverter design that creates seven levels (7L) at the output voltage using just a single voltage source.…”
Section: Introductionmentioning
confidence: 99%
“…cascaded H bridge (CHB) MLIs require more number of isolated sources and switching components. To reduce the device count, various symmetrical and asymmetrical MLIs [1][2][3][4] are presented. However, the MLIs [1][2][3][4] are unable to provide voltage gain which is essential in PV and EV applications.…”
mentioning
confidence: 99%
“…To reduce the device count, various symmetrical and asymmetrical MLIs [1][2][3][4] are presented. However, the MLIs [1][2][3][4] are unable to provide voltage gain which is essential in PV and EV applications. In recent times, switched capacitor MLI (SCMLI) topologies are widely used due to their simple operation and voltage gain features.…”
mentioning
confidence: 99%